Formulation and Physical Stability Evaluation of Herbal Liniment Containing Various Ginger Varieties (Zingiber officinale) - Aulia Fauziah Bening Hanani; Muhammad Arzam Fadhluddin Al Fikri; Melia Fitriana; Anugraheny Ayu Pramita; Rima Via; Farida Anwari; Herni Setyawati (Research and Social Study Institute, 2026)
Background: Musculoskeletal pain is a common health problem that can reduce the quality of life. Topical liniments are often used to relieve pain; however, long-term use of synthetic liniments carries a risk of skin irritation. Herbal-based liniments made from ginger rhizome (Zingiber officinale) are relatively safer, provide a warming sensation, and among their biological activities are anti-inflammatory and analgesic effects.Aims: This research aims to evaluation of herbal liniment identify containing various ginger varieties.Methods: This experimental study aimed to evaluate the physical stability of a herbal liniment with variations of ginger: red, gajah, and emprit. Three formulas were created, each containing 10% ginger extract in virgin coconut oil as a base. The evaluation was conducted over 28 days at room temperature (25 ± 2 °C), covering organoleptic properties, pH, homogeneity, viscosity, and transferable volume.Results: The results showed good physical stability: pH 5.00–5.66, viscosity 5.00–5.60 cP, maintained homogeneity, and volume >95%. Statistical analysis (p > 0.05) revealed no significant differences among the formulas. However, the dark brown color did not meet this standard.Conclusion: This herbal liniment is stable and has the potential to be developed as a topical preparation based on natural ingredients; however, color optimization is needed for better consumer acceptance.